Mengelola Batas dalam Konseling: Standar Menerima Hadiah - Aniyatussaidah, Aniyatussaidah; Marjo, H K (Jurnal Paedagogy, 2022)
The purpose of this study was to describe the explanation of gifts in counseling based on ethical and cultural considerations. The method in this research is a literature study, namely by collecting reading material from various scientific articles and then comparing theories and research results, which are then analyzed descriptively. Based on the results of a literature study conducted that counselors can receive gifts from counselees by considering aspects of culture, time of giving, and types of gifts given.